Expression of Wilms-tumor 1 antigen, vimentin and corticotropin releasing factor in human kidney with focal segmental glomerulosclerosis and effect of oxidative stress on these markers in HEK 293 cells - Roland Csurgyók; Gábor Sütő; István Wittmann; Tibor Vas (Karger Publishers, 2022)
Introduction: Wilms-tumor 1 antigen (WT1) expression in podocytes has the important role of maintaining their integrity and glomerular function. Vimentin also plays a role in preserving podocyte function and in morphologic changes observed after injury. Corticotropin releasing factor (CRF) is important in stress and in maintaining homeostasis. According to our previous studies, tyrosine (Tyr) isoforms (meta- and ortho-Tyr) may play a role in the development of many diseases. Introduction: Wilms-tumor 1 antigen (WT1) expression in podocytes has the important role of maintaining their integrity and glomerular function. Vimentin also plays a role in preserving podocyte function and in morphologic changes observed after injury. Corticotropin releasing factor (CRF) is important in stress and in maintaining homeostasis. According to our previous studies, tyrosine (Tyr) isoforms (meta- and ortho-Tyr) may play a role in the development of many diseases. Methods: Our aim was to investigate the expression of WT1, vimentin and CRF in human kidney and in HEK 293 cell cultures. Histological and clinical feature of 42 FSGS patients were evaluated and compared to patients with thin-basement membrane as a control group. Cells were cultured in medium containing para-, meta-, and ortho-tyrosine, and their expression of WT1, vimentin, and CRF were determined by immunocytochemistry. Podocyte foot process effacement was investigated by electron microscope (EM). Results: The intensity of WT1 staining in glomeruli was the same in focal segmental glomerulosclerosis (FSGS) and control groups, but it was lower in the tubulointerstitium of FSGS patients. Vimentin was lower in glomeruli of FSGS patients (p=0.009), and it was higher in the tubulointerstitium compared to the control group (p=0.003). CRF intensity was lower in the glomeruli (p=0.002). Podocyte foot process effacement determined by electron microscope (EM) showed correlation with vimentin and CRF in glomeruli. WT1 staining intensity was lower in meta- and ortho-Tyr group (p=0.001; p=0.009). Vimentin was lower in the meta-Tyr group (p=0.001). Discussion: Our observations on kidney biopsy samples support that the reduction of WT1 and vimentin could be characteristic for FSGS. Our results on HEK cells suggest that meta- and ortho-tyrosine may play a role in the development of FSGS.